ABOUT MORPHOLOGICAL FACTORS INFLUENCING THE ORIGIN OF THE FORMS OF A SIMPLE SENTENCE (Scientific journal of the Fergana State University, 2023)
The article examines the morphological factors influencing the emergence of forms of simple sentences in the Uzbek language. In particular, it analyzes the fact that the sentence has the smallest syntactic model [WPm] and its colorful features.